An empirical model accounting for added turbulence in the wake of a full-scale turbine in realistic tidal stream conditions. (November 2022) - Shariff, Kabir Bashir; Guillou, Sylvain S.
Abstract: The increased turbulence behind the turbine induces a fatigue load on the downstream turbine blades. An accurate estimate of turbulent intensity in turbine wake is paramount to optimizing the placement of turbines in tidal turbine parks. A simple empirical model is developed using data fitting from numerical simulation of a non-rotational actuator disc model to estimate the added turbulence in realistic tidal stream conditions similar to the Alderney Race, with a rotor diameter to depth ratio of 40%. The study shows a self-similar Gaussian shape streamwise turbulent intensity in a lateral direction similar to the velocity deficit profile. The turbulent wake radius expands according to a power-law depending on the ambient turbulent intensity. The added turbulence model justifies that the major turbulence source in the near wake is attributed to the rotor as it is weakly dependent on the ambient turbulence in the flow. As no known existing empirical model for tidal turbine wake added turbulence, the model is compared with existing models of unbounded wind turbines. The proposed model estimates the average turbulence in the far wake can assist turbine placement in a tidal farm. Highlights: Turbulent wake expands according to power law and depends on the turbulent intensity. High turbulent intensity facilitates faster recovery to ambient condition. Added turbulence is weakly affected by the ambient turbulence in the flow. The rotor is the major source of turbulence in the near wake. The proposed model estimates the average turbulence in the far wake.